Telemedicine and Plastic Surgery: Principles from the American Society of Plastic Surgeons Health Policy Committee. Issue 1 (20th May 2022) - Gfrerer, Lisa; Eberlin, Kyle R.; Figura, Laura; Freedman, Michael; Hadeed, Josef; Ver Halen, Jon; Perdikis, Galen; Zielinski, Marta; Patel, Ashit
Abstract : Summary: In the wake of the recent coronavirus disease of 2019 public health emergency, care delivery by means of telemedicine using audiovisual virtual platforms has become an important tool for patient communication. There are many logistic, medicolegal, and practical aspects of telemedicine that should be considered by the practicing plastic surgeon. Successful virtual patient interactions require an understanding of medical licensure requirements to perform telemedicine visits in a certain region. In addition, it is imperative to be familiar with specific liability and malpractice concerns, in addition to Health Insurance Portability and Accountability Act regulations before conducting electronic visits. During consultations, providers should be aware of proper physician conduct and the potential role of chaperones. Furthermore, appropriate visit documentation, in addition to telemedicine billing and coding, has to be ensured. Lastly, plastic surgeons should adhere to the rules of controlled substance prescription by means of telemedicine platforms. This article describes these salient topics surrounding telemedicine visits that are faced by plastic surgeons and discusses strategies to optimize and ensure safe use of virtual platforms.